The textual strategy and ideology of Psalm 36 - Botha, Phil J. (Old Testament essays, 2004)
Psalm 36 is a beautiful and masterfully crafted poem that once served to enhance the unity and conviction of a group of Yahwehworshippers. The strategy of the author seems to have been an attempt to create dissociation from a group of people who are described as 'wicked' and to promote association with Yahweh as their patron deity. The psalm probably served at the same time as a request to Yahweh to protect the members of the in-group against the arrogant behaviour of the out-group who had no respect for him. It ends with a statement of confidence in the eventual downfall of the wicked people.